Study Of Various Thermal Conductivity Layers in Bioheat Transfer Against Thermal Distribution on Human Skin with Finite Difference Method (FDM) - Wahyudi, Slamet; Ramadhan, Fakhrizal Azka (International Journal of Integrated Engineering, 2021)
Development of science are often found with the connection between science and another that forms a brands new science. one among the new sciences is biomechanics with one among its scientific fields is bioheat transfer which is applied to human skin. one among the factors that influence the heat propagation of skin tissue is thermal conductivity because the ability of materials to conduct heat. the aim of this study was to work out the mathematical model of bioheat transfer with a one-dimensional finite difference method and therefore the effect of thermal conductivity on its temperature distribution. The model is often made with combine the Pennes H.H equation to the steady state then the chosen parameter entered into it. The results of the study were compared between the finite difference method and therefore the analytic method. The results of comparative studies indicate a rise in temperature distribution but between the 2 still have differences (error). Changes in environmental temperature affect the temperature distribution in human skin. While the thermal conductivity of various layers has no significant effect, the worth of temperature distributed between points increases regularly from the core of the body to the outer layer of human skin